2021
DOI: 10.22456/1679-9216.114293
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Platelet Indices and Complete Blood Count in Canine Mammary Tumors

Abstract: Background: Malignant mammary tumors in humans and bitches cause hematological disorders such as anemia, erythrocytosis, thrombocytosis, hyperproteinemia, and leucopenia. Novel studies have been conducted on the predictive and prognostic values of platelet (PLT) indices in human breast cancer (HBC). However, there is little information about the alterations in hematological parameters in canine mammary tumors (CMTs). The aims of this study were to evaluate the platelet indices and complete blood count (CBC) pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Sorenmo et al (2000) suggested that OHE may be an effective adjunct to tumor removal in dogs with mammary gland carcinoma and that the timing of OHE plays a critical role in survival time. Although all female dogs are likely to develop neoplasm in the mammary gland as they advance in age, intact bitches have higher incidence of CMT (Uçmak et al, 2021). In addition, steroid hormones, mainly 17 beta-estradiol (E2) are involved in cell proliferation by exerting an antiapoptotic effect that favors tumor development (Canadas-Sousa et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Sorenmo et al (2000) suggested that OHE may be an effective adjunct to tumor removal in dogs with mammary gland carcinoma and that the timing of OHE plays a critical role in survival time. Although all female dogs are likely to develop neoplasm in the mammary gland as they advance in age, intact bitches have higher incidence of CMT (Uçmak et al, 2021). In addition, steroid hormones, mainly 17 beta-estradiol (E2) are involved in cell proliferation by exerting an antiapoptotic effect that favors tumor development (Canadas-Sousa et al, 2019).…”
Section: Discussionmentioning
confidence: 99%